On Numerical Methods for Robust Pole Assignment in Control System Design (Ⅱ) (Journal of Computational Mathematics, 2021)
L. R. Fletcher has pointed out that how to best exploit any freedom of choice in regard to the eigenvalues of a closed-loop system is an unsolved problem for robust pole assignment in control system design. This paper suggests a numerical method to solve this problem. Numerical results show that the method is feasible.